Non-selective laryngeal reinnervation in thyroid surgery - V. O. Palamarchuk; O. A. Tovkai; V. V. Voitenko; N. V. Solomennikova (Zaporožskij Medicinskij Žurnal)
Aim. To evaluate the results of the voice disorders correction in unilateral abduction paralysis of larynx by the anastomosis “ansa cervicalis – recurrent laryngeal nerve” during primary and repeated thyroid surgery.